A psychological challenge to qualitative philosophies: the weight of matter of insensible substance - Harold J. Cook (Galilæana)
Essay review of Barry Jonathan, Bigotti Fabrizio, eds. Santorio Santori and the Emergence of Quantified Medicine, 1614-1790. Corpuscularianism, Technology and Experimentation. Palgrave Studies in Medieval and Early Modern Medicine. Cham: Palgrave Macmillan-Springer, 2022.